STUDY OF AGITATION, COLOR AND STRESS LIGHT VARIABLES ON Spirulina platensis CULTURE IN A VERTICAL STIRRED REACTOR IN STANDARD MEDIUM - Solis-Mendez, A. [UNESP]; Molina-Quintero, M. [UNESP]; Oropeza-De la Rosa, E.; Cantu-Lozano, D.; Del Bianchi, V. L. [UNESP] (Univ Autonoma Metropolitana-iztapalapa, 2020)
Spirulina platensis is a helical-shaped photosynthetic cyanobacterium. Its cultivation depends on light intensity, nutrients, pH, cell density, temperature, among others. Microalgae are capable of growing in open and closed reactors. In the present work, it was studied microalgae Spirulina platensis growth in a stirred tank reactor (STR), evaluating stirring rate, color and light stress. Spirulina platensis was kept in flasks with Schlosser standard solution at room temperature, orbital shaker and fluorescent lamps. The operating conditions of stirred vertical reactors (vertical axis) were: LED light externally adhered to the reactor walls, four Rushton agitators, and 2.5 L of Schlosser standard solution inoculated with Spirulina platensis resulting in an initial concentration of 0.15 OD. Within the study of rate variable, the highest rate of 114 rpm, showed a productivity (P) of 2.08 mgL(-1)h(-1), concerning light color variable a high growth was observed in white light with a productivity of 2.85 mgL(-1) h(-1) and, regarding stress variable, Flash function showed a productivity 41% lower than standard white light. It was shown that stirring rate has a positive influence and light stress affects negatively the microalgae growth.
Keywords: Spirulina platensis; Stirring rate; light color; light stress; vertical reactor